Enhanced Recovery After Surgery Protocols in Major Urologic Surgery - Vukovic, Natalija; Dinic, Ljubomir (Frontiers in Medicine, 2018)
Abstract The purpose of the review: The analysis of the components of enhanced recovery after surgery protocols in urologic surgery. Recent findings: Enhanced recovery after surgery protocols (ERAS) has been studied for over twenty years in different surgical procedures, mostly in colorectal surgery. The concept of improving patient care and reducing postoperative complications was also applied to major urologic surgery and especially procedure of radical cystectomy. This procedure is technically challenging, due to a major surgical resection and high postoperative complication rate that may reach 65%. Several clinical pathways were introduced to improve perioperative course and reduce the length of hospital stay. These protocols differ from ERAS modalities in other surgeries. The reasons for this are longer operative time, increased risk of perioperative transfusion and infection, and urinary diversion achieved using transposed intestinal segments. Previous studies in this area analyzed the need for mechanical bowel preparation, postoperative nasogastric tube decompression, as well as the duration of urinary drainage. Furthermore, the attention has also been drawn to perioperative fluid optimization, pain management and bowel function. Summary: Notwithstanding partial resemblance between the pathways in major urologic surgery and other pelvic surgeries, there are still scarce guidelines for ERAS protocols in urology, which is why further studies should assess the importance of preoperative medical optimization, implementation of thoracic epidural anesthesia and analgesia and perioperative nutritional management.